A new complementary model for integrating historico- geographical and configurational approaches: The case of Famagusta - Allahmoradi, Mitra; Cömert, Nevter Zafter (International Seminar on Urban Form, 2021)
This paper presents a 'complementary model' for analyzing urban form by utilizing the historico-geographical and configurational approaches of urban morphology to achieve a better comprehension of the evolution of the urban form and, in particular, of the street formation of Famagusta. The results confirm that structurally the historico-geographical character and configuration of the town are determined by socio-economic activities. Within this context, both approaches identify the historical patterns of urban form as the key element to comprehend the relationship between socio-economic activity and urban form, which are both configurational and historical. Famagusta, a small historical town located in the eastern part of Cyprus, lacks a detailed urban morphological study and has been used to test this complementary method. The complementary model tested in Famagusta represents the strong relationship between land use and socio- economic activities, which determine how the urban form is transformed throughout the last six historical periods, and how socio-economic changes affected the urban form during these processes. Following political conflicts in the 1960s and the division of Cyprus in 1974, Varosha became the "ghost town" it remains to this day. These are the major hindrances to further development of the city toward the south. With the establishment of the Eastern Mediterranean University in 1979, the overall socio-economic structure of Famagusta has undergone rapid development. The Walled City remains intact and functioning, but is no longer the centre of socio- economic activity of the region, and the most integrated place in terms of global integration. © 2021 International Seminar on Urban Form. All rights reserved.
Keywords: Famagusta; historico-geographical approach; space syntax; street network; Urban form